PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN MEDIA FILM ANIMASI TERHADAP HASIL BELAJAR KOGNITIF SISWA SEKOLAH DASAR - Wahyu Rikha Rofikhatul Ula (Universitas Islam Nahdlatul Ulama Jepara, 2020)
This study aims to determine the effect of the animated film-aided problem solving model on the cognitive learning outcomes of grade IV elementary school students.The research method used in this study is a quantitative method in the form of Quasy Experimental Design. The design used in this study is Nonrandomized pretest-posttest control group design. The population in this study were all fourth grade students in the Kaliyetno Cluster environment, of which 136 were students. Determination of the sample in this study using purposive sampling technique. The sample in this study were grade IV students of SDN 1 Ternadi as the experimental class and SDN 2 Ternadi as the control class.The results of this study are: (1) There is an influence of problem solving models aided by animated film media on student cognitive learning outcomes. The results of the influence test show the Sig value of 0.00 <0.05, meaning that there is an influence of the problem solving model aided by animated film media on student cognitive learning outcomes; and (2) There are differences in the influence of problem solving models assisted by conventional film animation and learning media. This is indicated by the influence test using independent sample t-test showing a significance value of 0.00 <0.05. This proves that there are differences in the average value of cognitive learning outcomes of students in the experimental class and the control class after learning. Keywords: Animated Films, Cognitive Learning Outcomes, Problem Solving